Grand Bluewave Hotel Shah Alam / Mohd Ghadafi Mohtar ... [et al.] - Mohtar, Mohd Ghadafi; Sariman, Salwa; Hasnan, Noor Shazarina; Mohamed, Norhaida; Tajuddin, Nor Aziana (2001)
The quality of the personality and character needed for managerial position are no longer themselves sufficient for the conduct of a businees. In the present highly competitive world, they need to be supplemented by extensive specialist knowledge.